A CORRELATION BETWEEN STUDENTS READING HABIT AND THEIR ABILITY TO WRITE CAPTION ON INSTAGRAM - Ika Nurjanah (English Education Department Slamet Riyadi University Surakarta, 2023)
The present study entitled a correlation between students reading habit and their ability to write caption on Instagram on tenth grade students of SMK Wijaya Kusuma Surakarta. The aim of this study was to investigate whether there were a significant relationship between reading habit and ability to write caption. Qualitative method with correlation design was used collect the data. The instruments to obtain the data were reading habit and ability to write caption. To analyze the data, Person Product Moment formula was used in manual and computer calculations. Based on the data collected, the mean score of reading habit are 78.6 and the score of write caption are 62.8. The analysis showed that a coefficient ratio (rxy) of 0.088. Based on the result of this study, it can be conclude that there were a positive correlation between reading habit and their ability to write caption on Instagram on tenth grade students of SMK Wijaya Kusuma Surakarta. Keywords: Reading Habits, Writing Caption Ability, Correlation study, Instagram